Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Citra Perusahaan Terhadap Kepuasan Konsumen PT. FIFGROUP Cabang Jembe - Heri Setiawan; Hary Sulaksono; Haifa Haifa (JMBI : Jurnal Manajemen Bisnis dan Informatika, 2022)
The purpose of the study was to determine the effect of product quality, service quality and corporate image on customer satisfaction at PT FIFGROUP Jember Branch. The population in this study were consumers of PT FIFGROUP Jember Branch, amounting to 80 consumers who were used as respondents. The analytical model used in this study is multiple linear regression analysis. The results showed that partially product quality and service quality had an effect on consumer satisfaction, while the company image had no effect on consumer satisfaction. And simultaneously the three independent variables (product quality, service quality and company image) affect variable Y (customer satisfaction) PT FIFGROUP Jember Branch.